INTEGRATING LAW AND ECONOMICS IN INDONESIA - Maria GS Soetopo (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2019)
The application of “Law and Economics” dates back to 1,500 years ago, and has been applied in many eras. In the 20thCentury, Ronald Coase, pioneered the study of law and economics which was further elaborated by Richard Posner with a new synonimously interchangeable terminology,Economic Analysis of Law (EAL). EAL uses an economic method to analyze how changes in the law affect the allocation and distribution of wealth in society. This has provided a foundation of a market approach to the legal decision-making process through the use of varioustechniques including Cost Benefit Analysis (CBA), Cost Effective Analysis (CEA), and Regulatory Impact Assessment (RIA). As one of the most commonly used techniques, CBA quantifies the objectives of the law with an ultimate goal of maximizing benefits and minimizing costs. It is an analytical tool which searches for variables to indicate economic efficiency. As the legislative drafting process in Indonesia lacks a concrete and measured analytical tool, embedding the law and economics methodology within the regulatory making mechanism can provide more effective laws and regulations. As the world experiences uncertainties during the globalization era, it is imperative for any country to integrate law and economics in the regulatory governance framework to reach a common goal: the maximization of social welfare as enshrined in Article 33 of the 1945 Indonesian Constitution.